2017
DOI: 10.1021/acsomega.7b01438
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-β-cyclodextrin Inclusion Complex with β-Caryophyllene: Preparation, Characterization, and Improvement of Pharmacological Activities

Abstract: β-Caryophyllene (BCP) is a sesquiterpene that shows high potential in pharmacological applications. However, these have been drastically limited by the respective volatility and poor water solubility. The present study investigates the formation of inclusion complexes between BCP and methyl-β-cyclodextrin (MβCD) and shows that these complexes promote a significant improvement of the anti-inflammatory, gastric protection, and antioxidant activities relative to neat BCP. It is shown that the solubility of BCP is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 80 publications
4
22
0
Order By: Relevance
“…On the other hand, from the FTIR spectrum of the inclusion complex it is possible to observe the presence of bands at 1720.77 and 1641.25 cm −1 , the first characterized by the band of the C=O aldehyde carbonyl group and the second by the C=C alkene stretch, groups that are present in the citronella molecule. This result was found in the work of Santos et al [40], in which they performed the inclusion of the essential oil of citronella in cyclodextrin.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…On the other hand, from the FTIR spectrum of the inclusion complex it is possible to observe the presence of bands at 1720.77 and 1641.25 cm −1 , the first characterized by the band of the C=O aldehyde carbonyl group and the second by the C=C alkene stretch, groups that are present in the citronella molecule. This result was found in the work of Santos et al [40], in which they performed the inclusion of the essential oil of citronella in cyclodextrin.…”
Section: Resultssupporting
confidence: 71%
“…Figure 4a shows that the spectrum corresponding to citronella allows for observation of the presence of the vibrational mode of CH carbonyl bonded aldehyde and C=O carbonyl bonded aldehyde [40], with bands corresponding to 2856.20 and 1720.77 cm −1 , respectively. CH 2 asymmetric stretching and CH 3 asymmetric bending are also observed as bands in the regions 2917.91 and 1446.06 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The strong band was detected at 885 cm –1 in the BCP spectrum, which is assigned to out-of-plane deformation vibration of =CH distinctive of the BCP molecule. 31 However, this band is not observed in the spectrum of Rephyll ( Figure 4 b), maybe due to the constraint of the vibration because of the encapsulation process. At 858 cm –1 , a band was identified in the spectrum of Rephyll ( Figure 4 b), which characterized the distinctive composition of cellulose, which is presented in the NF.…”
Section: Resultsmentioning
confidence: 94%
“…Menezes et al indicated that (-)-linalool was successfully incorporated in β-cyclodextrin [14]. In a study conducted by Santos and coworkers it was shown that following inclusion of the sesquiterpene β-Caryophyllene in methyl-β-cyclodextrin, a significant improvement of biological properties were recorded [15].…”
Section: Non-invasive Skin Measurementmentioning
confidence: 99%